Intraocular Viral Communities Associated With Post-fever Retinitis - Arunasri, Kotakonda; Sai Prashanthi, Gumpili; Tyagi, Mudit; Pappuru, Rajeev R.; Shivaji, Sisinthy (Frontiers in Medicine, 2021)
The virome of the ocular fluids is naive. The results of the present study highlight the virome in the vitreous fluid of the eye of individuals without any ocular infection and compare it with the virome of the vitreous fluid of individuals with retinitis. A total of 1016037 viral reads were generated from 25 vitreous fluid samples comprising control and post fever retinitis (PFR) samples. The top 10 viral families in the vitreous fluids comprised of Myoviridae, Siphoviridae, Phycodnaviridae, Herpesviridae, Poxviridae, Iridoviridae, Podoviridae, Retroviridae, Baculoviridae and Flaviviridae. Principal coordinate analysis and heatmap analysis clearly discriminated the virome of the vitreous fluid of the controls from that of the PFR virome. The abundance of 10 viral genera increased significantly in the vitreous fluid virome of post fever retinitis group compared to the control group. Genus Lymphocryptovirus, comprising the human pathogen Epstein-Barr virus (EBV) that is also implicated in ocular infections was significantly abundant in 8 of the 9 vitreous fluid viromes of post fever retinitis group samples compared to the control viromes. Human viruses such as Hepacivirus, Circovirus and Kobuvirus were also significantly increased in abundance in the vitreous fluid viromes of post fever retinitis group samples compared to the control virome. The KEGG functional analysis and the network analysis depicted increase in the immune response by the host in post fever retinitis group compared to control group. Together the results of the study indicate changes in the virome in the vitreous fluid of patients with post fever retinitis group compared to the control group.